Rehabilitation Strategies and Behavioral Transformation of NAPZA Survivors at Yayasan Geratak Sambas - Listyaningrum, Indah; Zulkarnain, Zulkarnain (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
This study aims to analyze the social rehabilitation strategies for NAPZA (narcotics, psychotropics, and other addictive substances) survivors at Yayasan Geratak Sambas by applying the theoretical perspectives of Social Learning Theory, Labelling Theory, and Empowerment Theory. A qualitative descriptive approach was employed, involving in-depth interviews, participant observation, and documentation with survivors, facilitators, and foundation managers. The findings reveal that the rehabilitation process at Geratak Foundation operates through three main stages: (1) admission and initial assessment, (2) social and spiritual rehabilitation, and (3) social reintegration. These stages are implemented through a “therapeutic community” model that integrates spiritual guidance, social activities, and psychological counselling. Field data indicate that approximately 60% of survivors showed improved discipline and responsibility after three months of rehabilitation, 20% experienced significant emotional and social improvements within six months, while the remaining 20% continued to struggle with shame and social stigma despite showing psychological progress. These findings demonstrate that recovery is a gradual and nonlinear process influenced by social support and community acceptance. Through the lens of Social Learning Theory, behavioral changes occur via observation, imitation, and positive reinforcement within a supportive therapeutic environment. Labelling Theory highlights that social stigma poses a major barrier to reintegration, whereas Empowerment Theory emphasizes the importance of individual and community empowerment in fostering moral awareness, resilience, and social independence among survivors. Overall, the community-based rehabilitation strategy implemented by Yayasan Geratak Sambas has proven effective not only in behavioral recovery but also in promoting spiritual awareness, social solidarity, and identity reconstruction.